Adjustment unit price for dam proofing works in Raft, Pile Cap, H-steel and King Post of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding adjustment unit price for dam proofing works in Raft, Pile Cap, H-steel and King Post of BRAC University new campus project.